Perfil metabólico e nutricional de pacientes HIV positivos com lipodistrofia submetidos à terapia anti-retroviral: orientação nutricional - DUTRA, Cláudia Daniele Tavares (Universidade Federal do Pará, 2017)
Adverse effects of the lipodystrophyca syndrome is common in patients submitted to the use of highly active anti-retroviral therapy (HAART). This study evaluates the effectiveness of nutritional guidance on the metabolic changes in patients with lipodystrophy secondary to TARV, in the city of Belém - PA, in the period October 2006 to December 2007. We evaluated 29 patients, aged from 20 to 60 years, of both sexes, HIV positive, with lipodystrophyca syndrome, use of HAART and analyzed the metabolic and nutritional alterations before and after the intervention clinical-nutrition. The results were analyzed through programmes BioEstat 4.0 with p<0.05 and Virtual Nutri 1.0. We analyzed total cholesterol and fractions (LDL and HDL), triglycerides, insulin resistance, anthropometric measurements, measure of bone density, assessment of hepatic steatosis and cardiovascular risk. There was greater prevalence of patients retirees, male, aged 41 to 50 years and income from zero to three minimum wages. There were no significant differences between the sexes as to alcoholism and smoking, while 72% of patients not practiced physical activity. The association between lipoatrophy and lipohypertrophy and time of use of HAART, was significant, regardless of sex. There is total cholesterol and high triglycerides, low HDL and LDL normal. The analysis of the metabolism of carbohydrates, 48% of patients had changes glicêmicas and 34% resistance to insulin. It was observed that 52% of patients had hepatic steatosis and 79% change in bone mineral density, with greater prevalence for men. The syndrome presented lipoatrófica global measures smaller than the syndrome and mixed lipohipertrófica. After intervention clinical and nutritional changes significant decrease in levels of triglycerides and glucose and increase of HDL. As for cardiovascular changes, 31% of patients reduced the absolute risk of heart attack and death in 10 years, with reduction of total cholesterol and HDL. The nutritional intervention had a significant decrease in food intake of calories, proteins and lipids. Nutrition treatment minimized the metabolic changes of HAART, providing a better prognosis and quality of life of these patients.